If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -2(x + 3) = 0 Reorder the terms: 18 + -2(3 + x) = 0 18 + (3 * -2 + x * -2) = 0 18 + (-6 + -2x) = 0 Combine like terms: 18 + -6 = 12 12 + -2x = 0 Solving 12 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 0 + -12 -2x = 0 + -12 Combine like terms: 0 + -12 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| (8+4)*5+10-18+7+5*(7+1*4)+6= | | 4x-4x(4x-4x)= | | 4x^2-1=8x | | 7x-97=4x-13 | | 211-4x=32x+19 | | logy=1.6 | | 2x+x+400+2x=5000 | | x(x-20)=525 | | 75-2x=2x+19 | | -16-2x=-10x | | 3(x-2)-5(3-4x)=29-2x | | p^2-20-8p=0 | | (-2.6)+7=7+(-2.6) | | 20+8p=p^2 | | 9b+36=b^2 | | 6-(-15)= | | 3x=15y | | (-3y^2)(2xy)(-x)= | | 16X^3-24x^2-12x-14=0 | | (-3y^2)(2xy)= | | 2*(2+2)/2= | | 8x^2=7x | | f^2=10f-16 | | a^2+8a-9=0 | | (c-6)(c-3)=23 | | 5w*u*u= | | x(x-1)=x | | a(a-5)= | | 7x-14=48-14x-28 | | 2x+4=36-2x | | 2(x-2)=3(x+3) | | 7x-3y+14=0 |